KAJIAN EKSPERIMENTAL PENGARUH PANJANG CHORD SUDU TERHADAP UNJUK KERJA TURBIN HELIK UNTUK SISTEM PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) - Ahmad Rapa'i; Jorfri B Sinaga; M.Dyan Susila (Jurnal Ilmiah Teknik Mesin, 2014)
All this time microhydro power plants (MHP) created a resource use of  water flow has high fall of water (head) while for areas that have stream of river but do not have high fall of water (head) still a lot of untapped but has potential hydrokinetic be able rotating turbine. This is what lies behind the research conducted to determine the effect of chord length on the performance of the helical turbine which is expected to come helical turbine performance as the optimum use of the potential hydrokinetic. Helical turbine tested had dimensions of 1.2 m high and 1 m in diameter, blade profile NACA 0030, chord length 15 cm, 20 cm and 25 cm with number of blades 3 pieces. Tests performed on the irrigation canals that open to varying water velocity of 0.52 m/s, 0.68 m/s and 0.8 m/s. From the test results obtained helical turbine performance as follows. The largest torque obtained in water velocity of 0.52 m/s, 0.68 m/s and 0.8 m/s is 3.89 Nm, 27.09 Nm and 39.38 Nm is the chord length of the turbine with 25cm and the smallest torque on the chord length of 15 cm of 2.31 Nm. Power largest turbine in the water velocity of 0.52 m/s, 0.68 m/s and 0.8 m/s is 7.12 Watt, 60.41Watt and 103.96 Watt, turbine that is on the chord length of 25 cm and the smallest turbine power chord length of 15 cm by 3.58 watts. Largest turbine efficiency at water velocity of 0.52 m/s, 0.68 m/s and 0.8 m/s is 8.44%, 32.02% and 33.84% in the turbine with a chord length of 25 cm and efficiency the smallest turbines on the chord length of 15 cm of 1,17%. Keywords : microhydro, water turbine, helical turbine, chord length, helical turbine performance